Analysis of the 3D flow of an impinging jet on a slotted plate using TR-Tomo PIV and Proper Orthogonal Decomposition - Jana Hamdi (Energy Reports, 2020)
Impinging jets on plates with specific geometries, found in habitable enclosures, require a fundamental knowledge of the flow topology in order to reduce any acoustic or aeraulic discomfort. However, the flow in this type of jets is three-dimensional, time-dependent and turbulent. Thus, a high-speed volumetric velocity measurement technique is required to investigate the complete topology of the three-dimensional unsteady coherent flow structures. The research in the present paper has as aim the analysis of the flow from a volumetric point of view by using Time Resolved-Tomographic Particle Image Velocimetry (TR-TPIV) measurements. For this reason, an impinging jet on a slotted plate experimental set up has been developed and implemented. The kinematic fields of the studied volume are measured by TPIV acquisitions. Afterwards, the flow’s most energetic features were understood by the use of the snapshot Proper Orthogonal Decomposition (POD) technique which was applied on the kinematic fields. The results have shown that the first two modes were the most energetic and reflected the convective motion through the volume.